Association Between Genetic Polymorphisms of Metabolic Enzymes and Azathioprine-Induced Myelosuppression in 1,419 Chinese Patients: A Retrospective Study - Chen, Zhao-Yang; Zhu, Yang-Hui; Zhou, Ling-Yan; Shi, Wei-Qiao; Qin, Zhou; Wu, Bin; Yan, Yu; Pei, Yu-Wen; Chao, Ning-Ning; Zhang, Rui; Wang, Mi-Ye; Su, Ze-Hao; et al. (Frontiers in Pharmacology, 2021)
The aim of this study was to investigate the correlation between genetic polymorphisms of azathioprine-metabolizing enzymes and adverse reactions of myelosuppression. To this end, a retrospective analysis was performed on 1,419 Chinese patients involving 40 different diseases and 3 genes ITPA (94C>A), TPMT*3 (T>C), NUDT15 (415C>T). Strict inclusion and exclusion criteria were established to collect the relative cases, and the correlation between azathioprine and myelosuppression was evaluated by adverse drug reaction criteria. The mutation rates of the three genes were 29.32%, 3.73%, and 21.92%, and grades I to IV myelosuppression occurred in 54 (9.28%) of the 582 patients who took azathioprine. The highest proportion of myelosuppression was observed in 5 of the 6 (83.33%) patients carrying the NUDT15 (415C>T) TT genotype, and 12 of the 102 (11.76%) patients carrying the NUDT15 (415C>T) CT genotype. Only the NUDT15 (415C>T) polymorphism was found to be associated with the adverse effects of azathioprine-induced myelosuppression (odds ratio [OR], 51.818; 95% confidence interval [CI], 5.280–508.556; P = 0.001), which suggested that the NUDT15 (415C>T) polymorphism could be an influencing factor of azathioprine-induced myelosuppression in the Chinese population. Epistatic interactions between ITPA (94C>A) and NUDT15 (415C>T) affect the occurrence of myelosuppression. Thus, it is recommended that the genotype of NUDT15 (415C>T) and ITPA (94C>A) be checked before administration, and azathioprine should be avoided in patients carrying a homozygous NUDT15 (415C>T) mutation. This study is the first to investigate the association between genetic polymorphisms of these three azathioprine-metabolizing enzymes and myelosuppression in a large number of cases with a diverse range of diseases.